Dianetics [soundrecording] : the original thesis - Hubbard, L. Ron [ (La Fayette Ron)] , 1911-1986; Sherr, Lloyd (Golden Era Productions, 2007)
From the publisher's website: What is the dynamic principle of existence that drives all life forms? This question and much more is answered in this book. Discover the four "compartments" of your life. Discover what basic personality really is. Learn what the Analytical Mind is, its function and operation